MANAGEMENT OF HOUSEHOLD WASTES IN THE CITY OF CONSTANTINE BETWEEN ENVIRONMENTAL PROTECTION AND SUSTAINABLE DEVELOPMENT - Gherfi Sihem, (International Journal of Innovative Technologies in Social Science, 2024)
Indeed, the main objective of this study was to identify the management and treatment of household wastes in the City of Constantine, so as to reach environmental protection and attain sustainable development, due to the high quantity of household wastes and the resulting negative phenomena as a result of irrational management, which led to damaging the urban environment and public health; the fact of resulted in the necessity to develop the sector through moving towards the use of sustainable management methods, which has been highlighted in this paper through addressing the sustainable management of household wastes and comparing the same with the management in the city of Constantine, together with analyzing the results with applying some sustainable development indicators that measure good performance and effectiveness in this field, whereat it was concluded that the management in the city has shown to be a traditional management that relies on collection and sorting without recycling; and in the end discharging in landfills without any treatment.As a consequence, the efficiency of managing this type of wastes must be raised.